Correlation of overweight nutritional status and sleep quality in 16–18 years old teenagers in South Jakarta - Muhammad Prasetio Wardoyo; Bernie Endyarni Medise (Indonesian Nutrition Association, 2020)
Background and Objectives: Overweight nutritional status in adolescents becomes a health problem that continues to require attention. Not only because of its rapidly increasing prevalence, but also its various adverse effects on adolescent health, especially on the quality of sleep. Sleep quality decrease in adolescents can impact their daily performance, especially in learning. This study aimed to investigate the relationship of overweight nutritional status with sleep quality in adolescents aged 16–18 years old in South Jakarta.Method: This cross-sectional design study was done in two public senior high schools in the South Jakarta. A total of 186 students from classes of 2015, 2016, and 2017 with age between 16-18 years old underwent weight and height measurements, determination of BMI and nutritional status using the CDC BMI-for-age chart, as well as filling the Cleveland Adolescent Sleepiness Questionnaire to assess the quality of sleep.Results: The prevalence of overweight was found by 20.43% (14.52% categorized as overweight, 5.91% categorized as obese) with a median value of the questionnaire 40.00 (23.00 to 58.00). Mann-Whitney test found that the p value for the mean difference of the questionnaire's total score to excess weight is 0.783.Conclusion: There was no correlation between the quality of sleep to excess weight in adolescents aged 16–18 years old in South Jakarta.